Orthodoxy and enlightenment : George Campbell in the eighteenth century - Suderman, Jeffrey M. (Jeffrey Mark), 1965- (Montréal ; Ithaca : McGill-Queen's University Press, 2001)
Employing an interdisciplinary approach that gives equal consideration to Campbell's secular and religious writings, Jeffrey Suderman argues that Campbell used the critical tools of the Enlightenment to defend an orthodox Christian faith. This conclusion will oblige both historians and critics of the Enlightenment to reassess long-held assumptions about the secular nature of eighteenth-century thought and culture.
pt. I. George Campbell: life and works -- pt. II Natural Knowledge: the enlightened Campbell -- pt. III Revealed knowledge: the religious Campbell.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Campbell, George, -- 1719-1796.; Campbell, George, -- 1719-1796; Campbell, George (Philosoph); Philosophers -- Scotland -- Biography; Theologians -- Scotland -- Biography; Enlightenment -- Scotland; Scotland -- Intellectual life -- 18th century; Théologiens -- Écosse -- Biographies; Philosophes -- Écosse -- Biographies; Siècle des Lumières -- Écosse.; Écosse -- Vie intellectuelle -- 18e siècle.; BIOGRAPHY & AUTOBIOGRAPHY -- Religious; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; PHILOSOPHY -- Religious; Enlightenment; Intellectual life; Philosophers; Theologians; Scotland; Verlichting (cultuurgeschiedenis); Filosofie; Christendom; 1700-1799; Biographies